Situación actual de la oferta y demanda hídrica como servicio ambiental en la subcuenca yuracyacu. - Vela Navarro, Hans Cristhian (2008)
The research project has as its area of ​​influence the Yuracyacu sub-basin, which is an area of ​​collective importance, due to the fact that it contains important districts and populated centers such as the district of Nueva Cajamarca, which has a larger population and in which There is the greater economic activity the same that is located in the middle part of the sub-basin, followed by the Yuracyacu district located in the lower part and finally by populated centers of smaller population and socioeconomic activities. Reasons why, through inter-institutional agreements and local interests, work and research studies are carried out to minimize and prevent negative impacts and pressure on our natural resources and the water resources of this sub-basin, the result of one of the research studies Carried out is the present report. The research work is called "Current analysis of water supply and demand as a water environmental service in the Yuracyacu sub-basin", which presents the evaluation of the behavior and interaction of water supply and demand in the sub-basin, components that Influence it and the relation of existing; The results of this study will allow the implementation of proposals for necessary actions within the framework of water resource management, which will ensure the sustainable development of the area under analysis. The methodology used to carry out the current analysis of water supply and demand as a water environmental service in the Yuracyacu sub - basin was on the one hand the collection of secondary information in the sector 's institutions such as the Technical Cooperation of the German - GTZ, the Alto Mayo Special Project, the Technical Administration of the ATDR Irrigation District, the Nueva Cajamarca District Municipality and the Moyobamba EPS, as well as the collection of primary information that was through personal interviews with the plaintiffs of the water environmental service, In addition, it was very useful during the study, to resort to the geographic information system (GIS) as this tool could evaluate the existing water supply in the basin. It was concluded that the water supply in the sub-basin is 264271680 m3. This can satisfy the needs of drinking water of the population of the city of Nueva Cajamarca, but it is insufficient to satisfy the needs of water supply for irrigation, besides that the water demand is 114733444,91 m3, which for the moment is satisfied by the water supply existing in the sub-basin; As an index of the relationship between supply and demand, the use of the water scarcity index calculated is 43%, which denotes a High category, thus representing a strong pressure on the water resource, It also expresses a maximum urgency For the ordering of supply and demand and that the low availability of water is a limiting factor of economic development.